Early Initiation of Continuous Renal Replacement Therapy Induces Fast Hypothermia and Improves Post-Cardiac Arrest Syndrome in a Porcine Model. Issue 4 (October 2019) - Xu, Jiefeng; Chen, Qijiang; Jin, Xiaohong; Wu, Chunshuang; Li, Zilong; Zhou, Guangju; Xu, Yongan; Qian, Anyu; Li, Yulin; Zhang, Mao
Abstract : ABSTRACT: Rapid induction of hypothermia early after resuscitation can be an effective strategy against post-cardiac arrest syndrome (PCAS). Preliminary data suggested that continuous renal replacement therapy (CRRT) might be an efficient method to rapidly induce hypothermia. In this study, we investigated the efficacy of cooling induced by CRRT and its effects on the outcomes of PCAS in a porcine model. Thirty-two male domestic pigs weighing 36 ± 2 kg were randomized into 4 groups: sham control (n = 5), normothermia (n = 9), surface cooling (SC, n = 9), and CRRT (n = 9). Sham animals underwent the surgical preparation only. The animal model was established by 8 min of untreated ventricular fibrillation and then 5 min of cardiopulmonary resuscitation. At 5 min after resuscitation, the animals were cooled by either the combination of an earlier 8-h CRRT and later 16-h SC or the whole 24-h SC in the 2 hypothermic groups. For the other 2 groups, a normal temperature of 38.0 ± 0.5°C was maintained throughout the experiment. Blood temperature was decreased to 33°C within 28 min in animals treated with CRRT, which was significantly faster than that in the SC group requiring 185 min to achieve target temperature. Post-resuscitation myocardial dysfunction, brain injury, and systemic inflammation were significantly improved in the 2 hypothermic groups compared to the normothermia group. However, the improvement was significantly greater in the CRRT group than in the SC group. In conclusion, fast hypothermia was successfully induced by CRRT and significantly alleviated the severity of PCAS in a porcine model.